'What are girls made of?' A Critical Discourse Analysis - Rinawati Pelawi (UICELL, 2018)
Abstract This study is a critical discourse analysis towards an advertisement campaign by one of famous sport brands. Critical Discourse Analysis has been used mainly to examine how language is used to convey power and ideology in both written and oral discourse. There have been many studies on critical discourse analysis, however there is still lack of analysis on discourses such as advertisements campaign. Only until recently do major companies launch advertisements campaign dedicated to targeted consumers. The use of advertisement campaign may have been seen as effective to engage more with the audience, thus persuade the consumers into buying the products advertised. The use of CDA is suitable to dissect the advertisements to analyze power and ideology behind the adverts. This study used critical discourse analysis with research tool Fairclough three-dimensional model to examine an advertisement campaign published on social media, You Tube. The purpose is to examine the power and ideology conveyed in the advertisement as well as how language is used to convey them to the consumers. Keywords: advertisement campaign, critical discourse analysis, power, ideology ABSTRAK Penelitian ini adalah sebuah analisis wacana kritis sebuah kamapanye iklan dari salah satu produsen alat-alat dan pakaian olahraga terkenal. Analisis wacana kritis telah banyak digunakan utamanya untuk menganalisa bagaimana Bahasa dimanfaatkan untuk menunjukan ideologi dan kekuasaan dalam wacana lisan dan tulisan. Secara umum telah banyak penelitian dilakukan di ranah analisis wacana kritis ini, akan tetapi tidak banyak ditemukan analisis wacana kritis pada iklan-iklan berbentuk kampanye yang mengusung suatu tema. Sebelumnya tidak banyak perusahaan-perusahaan besar yang melakukan kampanye dalam iklannya, akan tetapi hal ini lebih banyak dilakukan sekarang dengan menyasar sekmen konsumen tertetnu. Kampanye iklan dipandang efektif oleh produsen-produsen untuk bisa lebih mendekatkan diri dengan konsumennya yang berdampak pada meningkatnya penjualan produk. Analisis wacana kritis mampu membedah kampanye iklan yang ada dan mengemukakan pesan yang terkandung di dalamnya. Penelitian ini menggunakan Fairclough model tiga dimensi untuk menganalisa suatu iklan yang ada di You Tube. Tujuan Analisa ini adalah untuk mengemukakan paham dan pesan yang terkandung di dalamnya. Kata kunci: kampanye iklan, analisis wacana kritis, paham, nilai